Enhancing Engagement and Relevance in Introductory Ict Courses for Non-Technical Students in Higher Education - Alton Mabina; Amber Mbotho (Amandemen: Journal of Learning, Teaching and Educational Studies, 2025)
This study investigates the challenges of engagement and relevance in introductory ICT courses for non-technical students, focusing on factors that contribute to student disengagement and strategies to enhance learning outcomes. The research objectives include examining the causes of negative attitudes toward ICT, analysing the disconnect between course content and students’ academic and career needs, and evaluating interdisciplinary teaching approaches that improve engagement. The study employs a mixed-methods approach, incorporating surveys and qualitative analysis of student experiences to assess existing pedagogical challenges. Findings indicate that rigid curricula, theoretical-heavy instruction, and a lack of application-based learning contribute to disengagement. Moreover, the study highlights the effectiveness of practical, interdisciplinary teaching strategies, such as project-based learning, gamification, and adaptive learning technologies, in fostering student interest and participation. The research concludes that aligning ICT education with real-world applications and diverse career pathways enhances student motivation, digital literacy, and employability. The study’s findings provide valuable insights for educators, curriculum developers, and policymakers to design more inclusive and effective ICT courses, ensuring that all students, regardless of their field, acquire essential digital competencies necessary for academic and professional success.